Theory and practice of constructive approaches in mathematics learning - Hanggara, Yudhi; Sa'dijah, Cholis; Qohar, Abdul (CAHAYA PENDIDIKAN, 2023)
The purpose of this study is to examine the theory and practice of constructivism in learning mathematics. This research is qualitative research using library research methods. Data was obtained by collecting various literature sources such as books, journals, and online research articles that are appropriate to the research problem. Data analysis in this study was carried out by content analysis. The research results show that teachers need to give students the freedom to experiment and provide relevant contexts for their theory development. In practice, teachers must consider that each student is unique and different in the way they understand and construct their knowledge. Therefore, teachers need to facilitate the learning process by considering the individual differences of students, ensuring that they have useful experiences and gain a deep understanding of the topics being taught.